Perancangan Alat Pemberi Pupuk Cair Aquascape Otomatis Menggunakan NodeMCU Berbasis Internet Of Things (IoT) - Moch Haidar Rafi; Bambang Santoso (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Aquascaping is an aesthetic art technique with the concept of arranging aquatic plants, rocks and wood in an aquarium. One of the most important factors in the success of maintaining Aquascape plants is the provision of liquid fertilizer, liquid fertilizer is needed by plants as nutrients so they can grow properly. Sometimes aquascape owners often experience busy work or other things that make aquascape owners forget to apply fertilizer to their aquascape plants. The purpose of this research is to design a liquid fertilizer application tool that can fertilize automatically based on the schedule set by the aquascape owner. It is hoped that by making an automatic liquid fertilizer application tool using NodeMCU based on the Internet of Things, it can make it easier for owners to apply fertilizer to their aquascape plants. The method to be used in this research is descriptive method or development research. With an automatic aquascape liquid fertilizer application using NodeMCU based on the Internet of Things, aquascape owners don't have to worry anymore when the owner is busy or traveling because the aquascape plants lack nutrients, and the liquid fertilizer application process can be done automatically so it can save time and become more practical..